sqrt(y-1)+sqrt(y-4)=sqrt(4y-11)

Simple and best practice solution for sqrt(y-1)+sqrt(y-4)=sqrt(4y-11) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for sqrt(y-1)+sqrt(y-4)=sqrt(4y-11) equation:


Simplifying
sqrt(y + -1) + sqrt(y + -4) = sqrt(4y + -11)

Reorder the terms:
qrst(-1 + y) + sqrt(y + -4) = sqrt(4y + -11)
(-1 * qrst + y * qrst) + sqrt(y + -4) = sqrt(4y + -11)
(-1qrst + qrsty) + sqrt(y + -4) = sqrt(4y + -11)

Reorder the terms:
-1qrst + qrsty + qrst(-4 + y) = sqrt(4y + -11)
-1qrst + qrsty + (-4 * qrst + y * qrst) = sqrt(4y + -11)
-1qrst + qrsty + (-4qrst + qrsty) = sqrt(4y + -11)

Reorder the terms:
-1qrst + -4qrst + qrsty + qrsty = sqrt(4y + -11)

Combine like terms: -1qrst + -4qrst = -5qrst
-5qrst + qrsty + qrsty = sqrt(4y + -11)

Combine like terms: qrsty + qrsty = 2qrsty
-5qrst + 2qrsty = sqrt(4y + -11)

Reorder the terms:
-5qrst + 2qrsty = qrst(-11 + 4y)
-5qrst + 2qrsty = (-11 * qrst + 4y * qrst)
-5qrst + 2qrsty = (-11qrst + 4qrsty)

Solving
-5qrst + 2qrsty = -11qrst + 4qrsty

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '11qrst' to each side of the equation.
-5qrst + 11qrst + 2qrsty = -11qrst + 11qrst + 4qrsty

Combine like terms: -5qrst + 11qrst = 6qrst
6qrst + 2qrsty = -11qrst + 11qrst + 4qrsty

Combine like terms: -11qrst + 11qrst = 0
6qrst + 2qrsty = 0 + 4qrsty
6qrst + 2qrsty = 4qrsty

Add '-4qrsty' to each side of the equation.
6qrst + 2qrsty + -4qrsty = 4qrsty + -4qrsty

Combine like terms: 2qrsty + -4qrsty = -2qrsty
6qrst + -2qrsty = 4qrsty + -4qrsty

Combine like terms: 4qrsty + -4qrsty = 0
6qrst + -2qrsty = 0

Factor out the Greatest Common Factor (GCF), '2qrst'.
2qrst(3 + -1y) = 0

Ignore the factor 2.

Subproblem 1

Set the factor 'qrst' equal to zero and attempt to solve: Simplifying qrst = 0 Solving qrst = 0 Move all terms containing q to the left, all other terms to the right. Simplifying qrst = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(3 + -1y)' equal to zero and attempt to solve: Simplifying 3 + -1y = 0 Solving 3 + -1y = 0 Move all terms containing q to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1y = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1y = 0 + -3 -1y = 0 + -3 Combine like terms: 0 + -3 = -3 -1y = -3 Add 'y' to each side of the equation. -1y + y = -3 + y Combine like terms: -1y + y = 0 0 = -3 + y Simplifying 0 = -3 + y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 4x-6(45-x)=-140 | | 39.95+.45x=59.95+.35x | | X^2-2x-1=x-3 | | 5x+11=121+(-6) | | -11n+8=-10n-10 | | 5x=121+6 | | 14=-13y+4y | | (X+1)(x-1)(x+2)=0 | | 4(x-3)-2(2x+1)=3(3x-4)-5(x-1)+9 | | 18x+8x-9x+10=? | | 14=-13y-4y | | -5-3k=19 | | 14-43=6(x-1)-5 | | 7x+12=10x+9 | | 4n+3=n-7 | | 234/3*x-30=906 | | 130*5/x+90=415 | | -6-4=9x+3-8x | | x/3+50=250 | | 60*15/x=100 | | 97+673-x=737 | | -24+4x=6-6(5+5x) | | 3-5x=21 | | 22*x=286 | | 3+5x=21 | | -5-3x=-32 | | (5x+10y+4)2= | | 23-4x=8 | | -2(-1+4n)=-7+n | | 4x^2-14=4x | | 4+8x=23 | | 4+18x=23 |

Equations solver categories